Independent evolutionary lineages in a globular cactus species complex reveals hidden diversity in a Central Chile biodiversity hotspot - Villalobos Barrantes, Heidy María (2022)
Unraveling the processes involved in the origin of a substantial fraction of biodiversity can be a particularly difficult task in groups of similar, and often convergent, morphologies. The genus Eriosyce (Cactaceae) might present a greater specific diversity since much of its species richness might be hidden in morphological species complexes. The aim of this study was to investigate species delimitation using the molecular data of the globose cacti “E. curvispina”, which harbor several populations of unclear evolutionary relationships. We ran phylogenetic inferences on 87 taxa of Eriosyce, including nine E. curvispina populations, and by analyzing three plastid noncoding introns, one plastid and one nuclear gene. Additionally, we developed 12 new pairs of nuclear microsatellites to evaluate the population-level genetic structure. We identified four groups that originated in independent cladogenetic events occurring at different temporal depths; these groups presented high genetic diversity, and their populations were genetically structured. These results suggest a complex evolutionary history in the origin of globular cacti, with independent speciation events occurring at different time spans. This cryptic richness is underestimated in the Mediterranean flora of central Chile, and thus unique evolutionary diversity could be overlooked in conservation and management actions.